Using collective impact to bring community change - Walzer, Norman; Weaver, Liz (Routledge, 2019)
Collective Impact as a tool to bring about community change has seen remarkable growth in usage since 2011. Collective Impact has been used successfully with a variety of local issues and has raised the consciousness of how community groups interact as well as the approaches that can lead to long-term innovations. This edited volume sets forth conceptual foundations for using Collective Impact as well as sharing basic approaches that have succeeded in projects under diverse circumstances. It will be useful for both academics and practitioners as Collective Impact continues to undergo substantial changes in focus and direction. Building on Kania and Kramer's influential work, it provides readers with detailed insights not only into how the Collective Impact system works but also innovative applications to issues facing community developers. The diverse topics shared by the contributing authors make this volume especially important for practitioners designing programs to bring about long-term changes in their communities. Including discussion about how Collective Impact has succeeded in different governmental settings, this book demonstrates how Collective Impact has been modified to accommodate the associated cultural differences with 10 chapters written by experienced on-the-ground community development experts
Keywords: Community development; Community organization